Intravitreal Conbercept Injection with and without Grid Laser Photocoagulation in the Treatment of Diffuse Diabetic Macular Edema in Real-Life Clinical Practice - Yule Xu; Ao Rong; Yanlong Bi; Wei Xu (Journal of Ophthalmology)
Purpose. To evaluate the efficacy of intravitreal conbercept (IVC) plus modified grid laser photocoagulation (MGP) versus IVC alone for treatment of diffuse diabetic macular edema (DDME). Methods. In this retrospective study, 51 DDME patients were treated with either IVC alone (IVC group) or IVC plus MGP (combined group) with 12 months of follow-up. The clinical records of those patients were reviewed. Results. 26 patients (31 eyes) received IVC alone and 25 patients (30 eyes) received combined therapy. At month 12, the mean best-corrected visual acuity (BCVA) letter score improvement was 9.1±4.5 and 7.5±4.2 in the IVC group and the combined group and the mean central retinal thickness (CRT) reduction was 145.1 ± 69.9 μm and 168.5±53.6 μm, respectively. There was no statistically significant difference of improvement in BCVA (P=0.164) and decrease in CRT (P=0.149) between the two groups. The mean number of injections delivered was significantly higher (P<0.001) in the IVC group (5.6 ± 0.8 per eye) than in the combined group (3.3±1.2 per eye). Conclusions. IVC alone or combined with MGP appeared to be effective for treatment of DDME, achieving the similar clinical efficacy. Moreover, MGP helps to reduce the number of injections.